Strategi Penyiaran Radio El John 95.9 fm Palembang Sebagai Media Pariwisata - Rivai, Muhammad Rizky Hidayat; Hasmawati, Fifi; Hamandia, Muhammad Randicha (Pubmedia Social Sciences and Humanities, 2024)
Radio El John 95.9 FM Palembang is one of the audio media in the city of Palembang. As the only radio that disseminates information about tourism, El John radio certainly has a strategy in its broadcasting. This is what makes researchers interested in finding out the broadcasting strategy for El John 95.9 FM Palembang radio as a tourism medium. This research uses a qualitative approach method. The theory used in this research is a theory developed by Phil Jones which dissects communication strategy into five stages, namely analysis and strategic planning (strategic analysis and planning), strategic design and implementation planning (strategic design amd implementation planning), launching or use of strategies (launching the strategy), follow-up and commitment (follow-up and commitment), and finally the provision of tracking strategies and results (embedding the strategy and tracking results). The results of the research concluded that El John radio, in its broadcast strategy as a tourism medium, makes great use of the latest technology to disseminate information, starting from conventional radio, radiostreaming online, radio apps, social media. In the broadcast, the announcer conveys information enthusiastically and cheerfully so that listeners are interested and enthusiastic about listening to the broadcast. Apart from that, the announcer also often uses interactive sentences, so that the listeners feel like they are being spoken to by the broadcaster. El John Radio also directs throughoutcrew to create tourism content when they are at tourist attractions in order to reach a wider audience so that the goal of El John radio to revive and preserve existing tourist attractions can be realized.